Increasing HIV/AIDS knowledge among urban ethnic minority youth: Findings from a community-based prevention intervention program. - Lardier, David T.; Opara, Ijeoma; Reid, Robert J.; Garcia-Reid, Pauline; Herrera, Andriana; Cantu, Irene (Journal of HIV/AIDS & Social Services, 2021)
HIV (Human Immunodeficiency Virus)/AIDs (Acquired immunodeficiency syndrome) prevention and research are imperative. Prevention-intervention programming is minimal in low-income communities of color. Additional research is needed that uncovers points of support and prevention to increase HIV knowledge and awareness and limit new HIV infections among adolescents of color. This study presents preliminary findings from a community-based HIV/AIDS, substance abuse, and viral hepatitis (VH) prevention education intervention for ethnic minority youth in a northeastern urban community. We evaluated HIV/AIDS knowledge and factors associated with knowledge. Participants (N = 599) completed a baseline survey followed by an exit survey measuring HIV/AIDS knowledge. Exit survey findings indicated that there was an increase in HIV/AIDs knowledge. Multivariate regression analyses showed that change scores in VH knowledge accuracy, sexual negotiation skills, risk perception, and ethnic identity were positively associated with change in HIV/AIDs knowledge score. The development and implementation of HIV/AIDS knowledge interventions can be crucial in alleviating new infections in the U.S.